Fulfillment Of Prisoners' Rights To Obtain Suitable Food According To Nutritional Needs Based On Law Number 22 Of 2022 Concerning - Nugroho, Ryan Setya Nugroho; Haerah, Kahar (Universitas Muhammadiyah Jember Press, 2024)
In the context of food in state detention centers or correctional institutions, it is regulated based on Law Number 22 of 2022 concerning Corrections regarding Corrections. The health and nutrition of prisoners must be considered in detail by technical implementers in food violations because in Article 9 letter d of Law Number 22 of 2022 concerning Corrections it is stated that prisoners have the right to receive adequate health and food services in accordance with nutritional needs, this must of course be carried out in accordance with the instructions and orders of the law. In this case, the Ministry of Law and Human Rights together with the Ministry of Health are reviewing further the fulfillment of the recommended RDA (Nutritional Adequacy Rate) according to age groups and nutritional requirements as well as for inmates with special needs. The problem raised in this article is how to fulfill prisoners' rights to receive adequate food in accordance with nutritional needs based on Law Number 22 of 2022 concerning Corrections? And, what are the legal consequences if prisoners' rights to receive adequate food according to nutritional needs are not fulfilled based on Law Number 22 of 2022 concerning Corrections? This type of research is empirical legal research. The data source comes from primary data. The results of this research are, First: Fulfillment of prisoners' rights to receive adequate food in accordance with nutritional needs based on Law Number 22 of 2022 concerning Corrections is stated in Article 9 letter d which confirms that prisoners have the right to receive adequate health services and food in accordance with nutritional needs. , this must of course be carried out in accordance with the instructions and orders of the law. Second, the legal consequences if prisoners do not fulfill their right to receive adequate food in accordance with their nutritional needs can be divided into administrative sanctions in the form of a written warning to employees/officials of the Pekanbaru Class II A Penitentiary who are negligent in fulfilling prisoners' rights to receive adequate and nutritious food, temporary dismissal to Employees/Officials of the Pekanbaru Class II A Penitentiary who are negligent in fulfilling prisoners' rights to receive adequate and nutritious food, and intensive supervision by the Indonesian Ministry of Law and Human Rights. As well as the consequences of criminal law, namely law enforcement of Article 2 paragraph (1) of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, if it is proven that there has been a deliberate budget cut by Class II A Pekanbaru Correctional Employees/Officials in fulfilling the prisoners' right to receive adequate food and nutritious.